2018
DOI: 10.1080/01621459.2018.1476242
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Semiparametric Functional Mixed Models for Serially Correlated Functional Data, With Application to Glaucoma Data

Abstract: Glaucoma, a leading cause of blindness, is characterized by optic nerve damage related to intraocular pressure (IOP), but its full etiology is unknown. Researchers at UAB have devised a custom device to measure scleral strain continuously around the eye under fixed levels of IOP, which here is used to assess how strain varies around the posterior pole, with IOP, and across glaucoma risk factors such as age. The hypothesis is that scleral strain decreases with age, which could alter biomechanics of the optic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…Lee, et al (2016) showed how to fit semiparametric FMMs that include smooth functional terms f ( X ia , t ) that are nonparametric in both x a and t . These terms can be directly accommodated in model (5) by specifying a fixed effect predictor that is linear in x a and a single random effect level whose design matrix Z h involves Demmler-Reinsch orthonormal spline basis functions (Demmler and Reinsch 1975) evaluated on X ia .…”
Section: Summary Of Functional Mixed Model Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Lee, et al (2016) showed how to fit semiparametric FMMs that include smooth functional terms f ( X ia , t ) that are nonparametric in both x a and t . These terms can be directly accommodated in model (5) by specifying a fixed effect predictor that is linear in x a and a single random effect level whose design matrix Z h involves Demmler-Reinsch orthonormal spline basis functions (Demmler and Reinsch 1975) evaluated on X ia .…”
Section: Summary Of Functional Mixed Model Frameworkmentioning
confidence: 99%
“…The form of the penalty for the FLAM involves just a scalar smoothing parameter and fixed penalty matrix, while the parameterization of the FMM can allow a broader class of regularization parameters, which can potentially yield more flexibility in modeling within-function correlations and also enables nonstationary structures, e.g. allowing the smoothing parameter of nonparametric term f ( x, t ) regulating smoothness of x to vary over k , which subsequently allows it to vary over t (Lee, et al 2016). …”
Section: Comparison and Contrast Of Flam And Fmmmentioning
confidence: 99%
See 3 more Smart Citations